2018
DOI: 10.4000/rga.5046
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Construction of a Socio-ecological Vulnerability Trajectory Based on the Quatre Montagnes (Isère, France) Area from 1950 to 2016

Abstract: This project was partially funded by LabEx ITEM and the GICC ADAMONT program. The authors extend their thanks to Marie-Pierre Arlot for the initiative and follow-up of this project, as well as François Véron for his contribution as an expert on the area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In the second stage, we applied a timeline analysis, which is a deductive qualitative method for the systemic and temporal analyses of the past trajectory of a SES (Bergeret et al 2015;Spiegelberger et al 2018). The chronosystemic timeline construction follows four steps.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second stage, we applied a timeline analysis, which is a deductive qualitative method for the systemic and temporal analyses of the past trajectory of a SES (Bergeret et al 2015;Spiegelberger et al 2018). The chronosystemic timeline construction follows four steps.…”
Section: Methodsmentioning
confidence: 99%
“…These drivers are shared characteristics of mountain SES and associated paradoxes of "Policies by outsider" and "in and out migration" (Klein et al 2019), along with ageing population (Ianni et al 2015). While many mountain regions have experienced similar trajectories (Locatelli et al 2017), other trajectories have been observed, particularly in terms of agricultural and tourism development (Spiegelberger et al 2018). For example, as few regions have been able to maintain agricultural activity, land abandonment is widespread in the Alps causing significant landscape transformation (Hinojosa et al 2019;Schirpke et al 2019).…”
Section: Drivers Of Change and Impacts On Nature Contributions To Peomentioning
confidence: 99%
“…The full implementation of the "chronosystemic timeline" approach presupposes the formation of a multidisciplinary team of researchers (Bergeret et al 2015;Spiegelberger et al 2018). This work was conducted by a multidisciplinary team of researchers (one ecologist, three social scientists) as recommended for the methodology, but due to the limited number of researchers, we applied a simplified version (Fig.…”
Section: Qualitative Approach: Chronosystemic Timelinesmentioning
confidence: 99%
“…The original and operational methodology used to depict the trajectory of a coastal SES proposed in this paper, which combines qualitative and quantitative information, proved to be particularly appropriate to reveal the dynamics of coevolution of the social and ecological components of a complex coastal system along with regime shifts. As recommended by Bergeret et al (2015) and Spiegelberger et al (2018), the trajectory of a SES must be studied using a holistic approach, calling on interdisciplinary expertise and using timelines as boundary objects between the natural sciences and social sciences. This holistic approach is in accordance with the theories developed by researchers studying complex systems (Holland This version of the article has been accepted for publication, after peer review but is not the Version of Record and does not reflect post-acceptance improvements, or any corrections.…”
Section: Perspectives For the Dynamic Analysis Of The Sesmentioning
confidence: 99%
See 1 more Smart Citation